Waste less time on Facebook — follow Brilliant.
×

Fake Proof's !!

Hey guys, here's a proof for 1=2. Can you find the Mistake !! a=b (say) a.a=b.b a.a=a.b a.a - b.b = a.b - b.b (a+b)(a-b) = b(a - b) a-b = b a = 2b b = 2b 1 = 2

Note by Pranav Pundarik
3 years, 3 months ago

No vote yet
1 vote

  Easy Math Editor

MarkdownAppears as
*italics* or _italics_ italics
**bold** or __bold__ bold

- bulleted
- list

  • bulleted
  • list

1. numbered
2. list

  1. numbered
  2. list
Note: you must add a full line of space before and after lists for them to show up correctly
paragraph 1

paragraph 2

paragraph 1

paragraph 2

[example link](https://brilliant.org)example link
> This is a quote
This is a quote
    # I indented these lines
    # 4 spaces, and now they show
    # up as a code block.

    print "hello world"
# I indented these lines
# 4 spaces, and now they show
# up as a code block.

print "hello world"
MathAppears as
Remember to wrap math in \( ... \) or \[ ... \] to ensure proper formatting.
2 \times 3 \( 2 \times 3 \)
2^{34} \( 2^{34} \)
a_{i-1} \( a_{i-1} \)
\frac{2}{3} \( \frac{2}{3} \)
\sqrt{2} \( \sqrt{2} \)
\sum_{i=1}^3 \( \sum_{i=1}^3 \)
\sin \theta \( \sin \theta \)
\boxed{123} \( \boxed{123} \)

Comments

Sort by:

Top Newest

a-b= 0 for a = b Then any number divided by zero is infinite so it is basically wrong

Allan Baguio - 3 years, 3 months ago

Log in to reply

In the step where u went from..... (a+b)(a-b)=b(a-b) so the next step should be a+b=b..... and then the next step a=0

Muzammil Abbas - 3 years, 3 months ago

Log in to reply

×

Problem Loading...

Note Loading...

Set Loading...